2020
DOI: 10.14202/vetworld.2020.2172-2177
|View full text |Cite
|
Sign up to set email alerts
|

Risk factors associated with stillbirth of piglets born from oxytocin-assisted parturitions

Abstract: Aim: The present study aimed to investigate the effects of different risk factors on stillbirth of piglets born from oxytocin-assisted parturitions. Materials and Methods: Data were collected from a total of 1121 piglets born from 74 Landrace x Yorkshire crossbred sows from a herd. Logistic regression models were used to determine the associations between stillbirth and different risk factors including parity (1, 2, 3-5, and 6-10), gestation length (GL) (112-113, 114-116, and 117-119 days), litter size, birth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

11
16
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 15 publications
(28 citation statements)
references
References 33 publications
11
16
0
1
Order By: Relevance
“…An inverse association between GL and stillbirth has been reported in several studies [2,8,14,17]. In this study, the quadratic effect of GL corroborates the result of the previous studies [2,23].…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…An inverse association between GL and stillbirth has been reported in several studies [2,8,14,17]. In this study, the quadratic effect of GL corroborates the result of the previous studies [2,23].…”
Section: Discussionsupporting
confidence: 92%
“…The stillbirth rate in this study is well in a range of the previously published results [2,6,9,[14][15][16]. Proportions of non-fresh (8.0%) and prepartum stillbirth (8.8%) in this study are in agreement with that in previous work, that is, 11.5% and 5.3%, respectively [5].…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…Definition of dystocia based on birth interval [2] may significantly elevate the dystocia rate in swine. Studies have shown that birth interval is associated with birthweight, stillbirth, piglet presentation, birth order, and litter size [5][6][7]. Hence, these factors may also be associated with dystocia.…”
Section: Introductionmentioning
confidence: 99%